Pengaruh Keramahan dan Keterbukaan Pengalaman terhadap Kinerja Karyawan yang Dimediasi oleh Knowledge Sharing pada PT. PLN (Persero) Distribusi Jawa Timur Area Pelayanan dan Jaringan Kediri - Suryariana, Sofia (BISMA (Bisnis dan Manajemen), 2018)
Economy development of globalization which is indicated by the rapid developments in information technology have an impact on the importance of human resource development-based knowledge sharing to support each activity within the organization. Every employee is required to be able to perform their jobs and adapt to the environment and the partners who have different personality traits of agreeableness and openness to experience. This study aims to examine and analyze whether this study aims to test and analyze whether the influence of agreeableness and openness to experience on performance of employees which were mediated by knowledge sharing at PT. PLN (Persero) Distribution of East Java Area Network and Services Kediri. The sampling technique of this study is using proportionate stratified random sampling with sample size of 55 respondents. Statistical analysis method was used Partial Least Square (PLS) with the help of the SMART PLS and SPSS 16.0 software. Based on the result of analysis showed that agreeableness and openness to experience has positive effect and significant impact on the knowledge sharing with value t-statistics of 2.934 and 7.739. Agreeableness and openness to experience has not positive effect and significant impact on the performance of employees with a value t-statistics of 1.867 and 1.751. Variable knowledge sharing has not positive effect and significant impact on the performance of employees with a value t-statistics of 1.075. The result showed that the value of agreeableness and openness to experience on knowledge sharing were 61.11 %, while the remaining 38.88 % effected by other variables. The influence of agreeableness, openness to experience and knowledge sharing on the performance of employees were 37.83 %, while the remaining 62.16 % effected by other variables.